2018
DOI: 10.1186/s12864-018-5258-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterisation of microRNAs and their target genes in phosphate-starved Nicotiana benthamiana by small RNA deep sequencing and 5’RACE analysis

Abstract: BackgroundPhosphorus is an important macronutrient that is severely lacking in soils. In plants, specific microRNAs (miRNAs) essential for nutrient management and the regulation of stress responses are responsible for the control of many phosphate starvation responses. Further understanding of conserved and species-specific microRNA species has potential implications for the development of crops tolerant to soils with low phosphate.ResultsThis study identified and characterised phosphate starvation-responsive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 67 publications
7
19
0
Order By: Relevance
“…Our results are consistent with sRNA sequencing data published for Arabidopsis [37,50] and Nicotiana benthamiana L. [72]. In both plant species, authors have shown that the number of various miR399 isomiRs was the most abundant in shoots and roots under low-Pi.…”
Section: Resultssupporting
confidence: 92%
“…Our results are consistent with sRNA sequencing data published for Arabidopsis [37,50] and Nicotiana benthamiana L. [72]. In both plant species, authors have shown that the number of various miR399 isomiRs was the most abundant in shoots and roots under low-Pi.…”
Section: Resultssupporting
confidence: 92%
“…In this work, the majority of DEMs represent various miR399 and miR827 isomiRs in both tested organs. Our results are consistent with sRNA sequencing data published for Arabidopsis [42,55] and Nicotiana benthamiana L. [93]. In both plant species, authors have shown that the number of various miR399 isomiRs was the most abundant in shoots and roots under low-Pi.…”
Section: Discussionsupporting
confidence: 92%
“…The well-known abiotic stress-responsive miR319c (21 nt) [6] was found to target various isoforms of GAMyb TF (HORVU3Hr1G079490, TargetSeek: score = 5, MFE = -34.6, PAREsnip2: score = 3, MFE = -35.4). The same predicted miR319 target has been previously found in RNA-Seq of Pi-starved tobacco plants [93]. Its targets, the plant GAMyb TFs, have been shown to activate gibberellin-responsive gene expression of α-amylase in barley [94,95].…”
Section: Pi-responsive Motifs Found In the Promoters Of Degssupporting
confidence: 68%
“…The use of phosphorus fertilizers has alleviated the problem, but it is rapidly depleted as a non-renewable natural resource, and lead to serious environmental pollution (Tong et al, 2017). Therefore, a substantial number of studies based on nextgeneration sequencing have documented the molecular responses of different plant species under Pideficient conditions (O′Rourke et al, 2013;Gho et al, 2018;Huen et al, 2018). Previously, we reported temporal transcriptome responses to Pi starvation in Masson pine seedlings and found that most transcripts were stably and gradually up-or downregulated within 48 d of Pi starvation (Fan et al, 2014).…”
Section: Discussion 10mentioning
confidence: 93%